To Buy or not to Buy? Shrouding and Partitioning of Prices in an Online Shopping Field Experiment - Markus Dertwinkel-Kalt; Mats Köster; Matthias Sutter (Center for Economic Studies and ifo Institute (CESifo), 2019)
We examine whether shrouding surcharges or partitioning prices raises demand in online shopping where consumers have very low costs of cancelling an initiated purchase process. In a field experiment with more than 34,000 consumers, we find that consumers in the online shop of a large German cinema initiate a purchase process more often when surcharges are shrouded or indicated separately, but they also drop out more often when the overall price becomes known at the check-out. In sum, the demand distribution is independent of the price presentation. This result qualifies previous findings on the effectiveness of such pricing practices and can be rationalized through low cancellation costs.
Keywords: D81; C93; 330; salience; inattention; shrouding; price partitioning; field experiment